2010
DOI: 10.1103/physreve.82.026319
|View full text |Cite
|
Sign up to set email alerts
|

Second-order structure function in fully developed turbulence

Abstract: 10We relate the second order structure function of a time series with the power spectrum of the original variable, taking an assumption of statistical stationarity. With this approach, we find that the structure function is strongly influenced by the large scales. The large scale contribution and the contribution range are respectively 79% and 1.4 decades for a Kolmogorov -5/3 power spectrum. We show numerically that a single scale influence range, over smaller scales is about 2 decades. We argue that the stru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(107 citation statements)
references
References 32 publications
8
99
0
Order By: Relevance
“…Nam et al [33] theoretically showed that when the Ekman friction is present, the forward enstrophy cascade is then intermittent [34]. As already mentioned above this result is difficult to verify experimentally by using the conventional structure function analysis since the convergence condition requires the scaling exponent β of the Fourier spectrum, i.e., E(k) ∼ k −β , to be in the range (1,3) [1,12,32], see also discussion in Sec. III.…”
Section: Introductionmentioning
confidence: 99%
“…Nam et al [33] theoretically showed that when the Ekman friction is present, the forward enstrophy cascade is then intermittent [34]. As already mentioned above this result is difficult to verify experimentally by using the conventional structure function analysis since the convergence condition requires the scaling exponent β of the Fourier spectrum, i.e., E(k) ∼ k −β , to be in the range (1,3) [1,12,32], see also discussion in Sec. III.…”
Section: Introductionmentioning
confidence: 99%
“…In future work we plan to consider multifractal properties of pH fluctuations, using structure functions or, to avoid perturbation by energetic large scales (Huang et al, 2010), recent methods based on empirical mode decomposition .…”
Section: Discussionmentioning
confidence: 99%
“…The dotted lines correspond to power laws of slope 0.2 and 0.3, corresponding respectively to active or passive scalar turbulence (Monin and Yaglom, 1975) (see below). The scaling range is limited here, possibly due to contamination from periodic forcing, which may destroy the scaling of structure functions but is less problematic in the Fourier space (see Huang et al, , 2010. …”
Section: Ph Pdfsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since surface waves often occupy the same frequency range as marine turbulence, it is difficult to separate the latter from waveinduced velocity fluctuations using simple filtration. Therefore, development of various techniques and methods capable to remove the bias produced by surface waves from ADCP measurements of turbulent shear stress was an important issue over the past decade (Shaw and Trowbridge, 2001;Trowbridge and Elgar, 2003;Whipple et al, 2006;Feddersen and Williams, 2007;Rosman et al, 2008;Schmitt et al, 2009;Huang et al, 2010;Kirincich et al, 2010). This paper addresses two challenges.…”
Section: K a Korotenko Et Al: Effect Of Variable Winds On Current mentioning
confidence: 99%